Sustaining the growth of rural SMEs: effect of financial access and entrepreneurial characteristics on business performance in a Felda scheme In Pahang - Mohd Sauh, Shuhaimi; Abdullah, Moha Asri; Abdul Rahman, Rozailin (Global Academic Excellence, 2021)
In Malaysia, Small and Medium Enterprises (SMEs) contribute more than one third to the country’s gross domestic product (GDP). Past studies revealed that access to finance and entrepreneurial characteristics are often known as predictors of SMEs performance. Nonetheless, access to finance is still one of the pressing problems faced by SMEs in Malaysia. Studies on this topic have not been extensively explored particularly in the FELDA scheme. Hence, this paper attempts to investigate how access to finance and entrepreneurship characteristics affect SMEs business performance in the FELDA scheme. This study employed a survey research design. Data were collected from a sample of 368 SMEs and analysed using the Structural Equation Modelling (SEM).T his study found the insignificant effect of access to finance on business performance. There was no significant effect of innovativeness and proactiveness on business performance. Interestingly, risk-taking was directly related to SMEs business performance. Overall, findings imply that SMEs in the FELDA scheme have difficulties getting financial access, dare to take bold actions in business but they are lacking the propensity in introducing new business ideas and are not fast enough in taking advantage of new business opportunities. The paper recommends that government agencies should provide adequate business support and financial access to improve SMEs entrepreneurial capabilities and business performance.